The Influence of Supplemental Multi-enzyme Feed Additive on the Performance, Carcass Characteristics and Meat Quality Traits of Broiler Chickens - Zakaria, Hana A.H.; Jalal, Mohammad A.R.; Ishmais, Majdi A. Abu (International Journal of Poultry Science, 2010)
A study was conducted to investigate the effect of adding a commercial multienzyme feed additive (Tomoko, Biogenkoji Research Institute, Japan) on the performance of broilers. Four isoenergetic and isontirogenous diets consisting of control diet without enzyme (Con) and three test diets supplemented with Tomoko at 250 (T250), 500 (T500) and 750 (T750) g/tonne of feed were used for starter, grower and finisher phases. Each diet was offered to 10 replicates of 40 one-day-old straight-run Lohmann broiler chicks (n = 1600) in a randomized complete block design (10 blocks of 4 diets each). Data was analyzed using mixed procedure of SAS (repeated measures analysis) for a randomized complete block design, with level of significance set at p = 0.05. Enzyme used in the study was authenticated by the supplier to have minimum level of acidic protease (10,000 U/g), alpha-amylase (40 U/g), pectinase (30 U/g), phytase (10 U/g), glucoamylase (5 U/g) and cellulase (4 U/g). Enzyme supplementation had no significant effect on Feed Intake (FI) at 21 d, while at 42 d birds fed T250 and Con diets significantly consumed more feed than T500 and/or T750. No significant differences were observed for Feed Conversion Ratio (FCR). Body Weight (BW) and Body Weight Gain (BWG) were significantly higher (p